Design, Synthesis and Anticancer Activity of Novel Substituted (E)-2-Morpholinoquinoline- 3-carbaldehyde-O-((-1-aryl-1H-1,2,3-triazol-4-yl)methyl)oxime Derivatives - Chatla, Aruna Jyothi; Yerrabelly, Jaya Praksh Rao; Dharavath, Nagaraju; Shyam, Panga (Asian Journal of Chemistry, 2024)
A new series of substituted (E)-2-morpholinoquinoline-3-carbaldehyde-O-((-1-phenyl-1H-1,2,3-triazol-4-yl)methyl)oxime scaffolds were synthesized from involving alkynyl quinoline oximes with various aryl azides by click reaction obtained corresponding compounds with high yields. The synthesized compounds were characterized by using IR, 1H NMR, 13C NMR and HRMS data. All the synthesized compounds screened anticancer activity against MCF-7, HeLa, PC-3 cell lines. All the compounds exhibited good results among them 8b, 8g and 8i compounds have shown prominent anticancer activity are compared to standard drug doxorubicin.